Change in Subduction Dip Angle of the Indian Continental Lithosphere Inferred From the Western Himalayan Eclogites - Chen, Si; Chen, Yi; Guillot, Stéphane; Li, Qiuli (Frontiers in Earth Science, 2022)
The occurrence of ultrahigh-pressure (UHP) and high-pressure (HP) rocks in the Himalayan orogen has been conventionally attributed to the different subduction dip angles along the strike. The western Himalayan UHP eclogites point to a steep continental subduction in the Eocene. The present-day geophysical data show low subduction dip angles of the Indian lithosphere beneath southern Tibet and Karakoram, implying that a shift from steep to low-angle subduction probably happened in the western Himalaya. However, the timing and mechanism of such a subduction-angle change are still unknown. Here we present a combined analysis of zircon geochronology and geochemistry of eclogites and gneiss in the Stak massif, western Himalaya. Metamorphic zircons equilibrated with garnet and omphacite show flat heavy rare earth element patterns without Eu anomalies and, thus, yield similar eclogite-facie ages of ca. 31 Ma. The Stak HP eclogite-facie metamorphism is at least 15 Ma younger than those measured in the western Himalayan UHP eclogites, but broadly contemporaneous with other Himalayan HP rocks. Therefore, all the Himalayan HP rocks record higher peak geothermal gradients and younger ages than those of the UHP rocks. Our new data, combined with the magmatic lull observed in the Kohistan–Ladakh–Gangdese arc and with the convergent rate of the Indian plate, suggest a change in subduction dip angle over time. Consequently, we suggest that the entire Indian continental lithosphere experienced an approximately coherent shift from steep to low-angle subduction after the breakoff of the Neo-Tethyan slab since the middle Eocene. This critical change in subduction geometry is interpreted to be responsible for the transition from continental subduction to collision dynamics.